2019
DOI: 10.31234/osf.io/9c3s2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Humanizing pedophilia as stigma reduction: A large-scale intervention study

Abstract: The stigmatization of people with pedophilic sexual interests is the topic of growing academic and professional consideration, owing to its potential role in moderating pedophiles’ emotional wellbeing, and motivation and engagement in child abuse prevention schemes. Thus, improving attitudes and reducing stigmatization toward this group is of paramount importance. Prior research has suggested that narrative humanization – presenting personal stories of self-identified non-offending pedophiles – could be one ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…To explore the presence of stigmatized attitudes toward MAPs among healthcare professionals, we compared SPS scores within the current sample to those obtained from a large-scale public investigation whereby data were made available (Harper et al, 2021). This analysis was conducted to estimate the levels of stigma among professional groups.…”
Section: Stigma and Knowledge About Pedophiliamentioning
confidence: 99%
See 3 more Smart Citations
“…To explore the presence of stigmatized attitudes toward MAPs among healthcare professionals, we compared SPS scores within the current sample to those obtained from a large-scale public investigation whereby data were made available (Harper et al, 2021). This analysis was conducted to estimate the levels of stigma among professional groups.…”
Section: Stigma and Knowledge About Pedophiliamentioning
confidence: 99%
“…That is, previous work has highlighted that anticipated stigma is a barrier to MAPs seeking professional support (Grady et al, 2019;Levenson & Grady, 2019b), but there has been scant empirical attention paid to the actual levels of stigmatization among professional groups; nor has this stigma been broken down into its component domains of dangerousness, choice, and deviance attributions, alongside punitive attitudes. There has been a substantial amount of research published into public stigmatization of MAPs (e.g., Harper et al, 2018Harper et al, , 2021Jahnke et al, 2015a, b) with high levels of stigma being reported. As such, we selected the public as a baseline level of stigma to compare the scores of professionals against, as MAPs are likely using societal stigma as a basis for their concerns.…”
Section: Stigma and Knowledge About Pedophiliamentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the prevalence of stigmatized attitudes towards MAPs among healthcare professionals we compared SPS scores within the current sample to those obtained from a large-scale public investigation whereby data were made available (Harper et al, 2021). We sampled a random selection of 110 participants from the public dataset to ensure approximately equivalent sample samples across each cell of our analysis before conducting a series of one-way analyses of variance (ANOVAs) to explore between-groups differences on each stigma domain.…”
Section: Attributions Knowledge and Stigmamentioning
confidence: 99%